Odpowiedzi

Najlepsza Odpowiedź!
2009-10-04T17:01:17+02:00
C) A = <2,6) , B = <6, 7 >
AυB =<2,7>
AnB =pusty zbior
A/B =A

d) A = ( -∞, 4 ) , B = <0, +∞ >
AυB=(-∞,∞)
AnB=<0,4)
A/B =(-∞,0)
e) A = ( -1,4 > , B = <2,5>
AυB=(-1,5>
AnB=<2,4>
A/B =(-1,2)
f) A = ( - 2,1), B = <1, 4 )
AυB=(-2,4)
AnB=pusty zbior
A/B =A
g) A = ( -∞, 6 > , B = (4, 7 >
AυB=(-∞,7>
AnB=(4,6>
A/B=(-∞,4>
h) A = ( 2,+∞), B = ( -∞,3>
AυB=(-∞,∞)
AnB=(2,3>
A/B =(3,∞)
1 4 1
2009-10-04T17:01:23+02:00
Odpowiedzi wg kolejnosci z tresci

c) A = <2,6) , B = <6, 7 >
<2,7>
pusty
<2,6)

d) A = ( -∞, 4 ) , B = <0, +∞ >
(-∞;+∞)
<0, 4)
(-∞, 0)

e) A = ( -1,4 > , B = <2,5>
(-1, 5>
<2,4>
(-1,2)

f) A = ( - 2,1), B = <1, 4 )
(-2, 4)
pusty
( - 2,1)

g) A = ( -∞, 6 > , B = (4, 7 >
(-∞, 7>
(4, 6>
(-∞, 4>

h) A = ( 2,+∞), B = ( -∞,3>
(-∞, +∞)
(2,3>
(3, +∞)
1 5 1
2009-10-04T17:03:09+02:00
C) A = <2,6) , B = <6, 7 >
AυB =<2,7>
AnB =pusty zbior
A/B =A

d) A = ( -∞, 4 ) , B = <0, +∞ >
AυB=(-∞,∞)
AnB=<0,4)
A/B =(-∞,0)

e) A = ( -1,4 > , B = <2,5>
AυB=(-1,5>
AnB=<2,4>
A/B =(-1,2)

f) A = ( - 2,1), B = <1, 4 )
AυB=(-2,4)
AnB=pusty zbior
A/B =A

g) A = ( -∞, 6 > , B = (4, 7 >
AυB=(-∞,7>
AnB=(4,6>
A/B=(-∞,4>

h) A = ( 2,+∞), B = ( -∞,3>
AυB=(-∞,∞)
AnB=(2,3>
A/B = (3,∞)

i chyba tyle :D